SUBSYSTEM "EMPLOYEE" IN THE MANAGEMENT SYSTEM OF OCCUPATIONAL HEALTH AND SAFETY AT THE ENTERPRISE (World Science, 2020)
Theoretical principles of approaches to solving the problem of reducing injuries and improving working conditions are considered. It is shown that the complexity of the issue of ensuring an effective level of employee safety requires the use of multifactorial research methods. The presented results in the theoretical research proved the necessity and possibility of using the theory of systems analysis in combination with the theory of automatic control and the theory of reliability to achieve this goal. It is determined that the working conditions and tasks set by managers to employees in the 21st century are increasingly becoming formalized (determined). Workers on safety issues must follow rules that limit their activity, and this has an impact on their behavior. It is determined that the working conditions and tasks set by managers to employees in the 21st century are increasingly becoming formalized (determined). Workers on safety issues must follow rules that limit their activity, and this has an impact on their behavior. It has been proven that possible disturbances and opposition to the implementation of these rules and restrictions should be taken into account. It is necessary to register all errors and deviations from the normal condition of the employee, starting with the most minor ones.  It is shown that the safety management system is based on the efficient and error-free operation of the subsystem "employee", which is probabilistic (by the nature of its origin), that is, errors can occur in the work. It is pointed out that it is necessary to take into account all the components of the dualistic management scheme of the occupational safety and health management system. It is emphasized that it is necessary to revise all instructions on labor protection taking into account the risks of non-compliance with safety requirements and taking into account their consequences. Attention is drawn to the fact that automatic control systems in automatic control systems must be implemented in the production to ensure the registration of error-free operation of workers, and provide them with assistance in case of difficult production situations.